407 Preliminary safety, pharmacokinetics/pharmacodynamics, and antitumor activity of XmAb20717, a PD-1 x CTLA-4 bispecific antibody, in patients with advanced solid tumors. (10th December 2020) - Shum, Elaine; Daud, Adil; Reilley, Matthew; Najjar, Yana; Thompson, John; Baranda, Joaquina; Donald Harvey, R; Leidner, Rom; Shields, Anthony; Cohen, Ezra; Cohen, Roger; Mita, Alain; et al.
Abstract : Background: XmAb20717 is a humanized bispecific monoclonal antibody that simultaneously targets PD-1 and CTLA-4. We report preliminary data from an ongoing, multicenter, Phase 1 study investigating the safety/tolerability, pharmacokinetics/pharmacodynamics, and clinical activity (RECIST 1.1) of XmAb20717 in patients with selected advanced solid tumors. Methods: A 3+3 dose-escalation design was used to establish a maximum tolerated (MTD)/recommended dose for evaluation in parallel expansion cohorts, including melanoma, renal cell carcinoma, non-small cell lung cancer (NSCLC), prostate cancer, and a basket of tumor types without an FDA-approved checkpoint inhibitor (CI; n≤20 each). XmAb20717 was administered as an infusion on Days 1 and 15 of each 28-day cycle. Results: As of 08Jul2020, 109 patients had been treated (table 1 ), and 30 were continuing treatment. In escalation, 6 dose levels (0.15–10.0 mg/kg) were evaluated (n=34); an MTD was not established. Expansion cohorts were initiated at 10 mg/kg (n=72), and a 15 mg/kg escalation cohort was added (n=3). T-cell proliferation was noted in peripheral blood at doses as low as 3 mg/kg and was highest at 10 mg/kg. At this dose, consistent proliferation of CD8+ and CD4+ T cells was observed, indicative of dual PD-1 and CTLA-4 checkpoint blockade (figure 1 ). Paired pre- and post-dosing biopsies showed increased intratumoral T-cell infiltration and IFN-response signatures following treatment. Grade 3/4 treatment-related adverse events (TRAEs) reported for ≥3 patients included rash (13%), transaminase elevations (7%), lipase increased (4% [2% with amylase increased]), and acute kidney injury (3%), all considered immune-related. There were 2 Grade 5 TRAEs: immune-mediated pancreatitis (in the presence of pancreatic metastases) and immune-mediated myocarditis (Grade 4) that contributed to respiratory failure. A complete response was reported as the best overall response for 1 patient (melanoma); partial responses were reported for 5 patients (2 melanoma, 2 NSCLC, 1 ovarian). The objective response rate was 13% overall and 21% at 10 mg/kg (6/46 and 6/29 evaluable patients, respectively). All responders had prior CI exposure. Responses were observed only at 10 mg/kg and, within the 10 mg/kg group, appeared to correlate with higher peak serum concentration and area under the curve. Conclusions: XmAb20717 induced T-cell proliferation in peripheral blood consistent with dual-checkpoint blockade. Preliminary data indicate XmAb20717 was generally well-tolerated and associated with evidence of antitumor activity in CI-pretreated patients with various types of advanced solid tumors. Trial Registration: NCT03517488 Ethics Approval: The study was approved by each institution's IRB.